PELAYANAN KESEHATAN RUMAH SAKIT UMUM DAERAH TERHADAP PASIEN BPJS DI KABUPATEN KUANTAN SINGINGI - Ahmad Rikal; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Health is a basic need of every human being and is the capital of every citizen and every nation in achieving its goals and achieving prosperity. Service is an activity or sequence of activities that occur in direct interaction between a person and another person or a physical machine, and provides customer satisfaction. The purpose of this study was to find out and evaluate the implementation of the Minimum Standards for Health Services implemented by the Kuansing District Hospital efficiently and effectively in accordance with the provisions of the Kuansing Regent Regulation Number 39 of 2018 concerning the Minimum Standards of Health Services. The type of research used in this study is a qualitative research method. Qualitative research does not intend to describe the characteristics of the population or draw generalizations of conclusions that apply to a population, but rather focuses on the representation of social phenomena. Qualitative research departs from assumptions about reality or social phenomena that are unique and complex. The data collection carried out was an interview process conducted directly at the Kuansing District Hospital. The results showed that the implementation of health services was not yet optimal in accordance with the minimum service standards at the Kuantan Singingi District Hospital, caused by several factors, namely the limited cost factor due to several years of nomenclature errors. budget in the Kuantan Singingi Regency APBD, resulting in arrears in payment claims to BPJS Health. Due to the limited cost factor, it directly causes health facilities and infrastructure factors that cannot be provided, such as medicines and medical equipment peralatan Keywords : Administration, BPJS, Service, Easy,Cheap, Rousing